Homologous MXene‐Derived Electrodes for Potassium‐Ion Full Batteries (Adv. Energy Mater. 23/2022). Issue 23 (16th June 2022) - Sun, Lanju; Sun, Jikai; Zhai, Shengliang; Dong, Tiantian; Yang, Hongyan; Tan, Yi; Fang, Xu; Liu, Chengcheng; Deng, Wei‐Qiao; Wu, Hao
Abstract : Potassium‐ion Batteries The development of potassium‐ion battery (PIB) electrode materials is vital to next‐generation energy storage. In article number 2200113, Hao Wu and co‐workers propose an unlocking metal‐organic framework (MOF) node strategy to increase the K + adsorption energy, leading to significantly improved K + storage capacity. Moreover, a PIB is assembled with a homologous MXene‐derived MOF anode and a K + ‐intercalated vanadium oxide cathode.